Student Loan Information Provision and Academic Choices - Schmeiser, Maximilian; Stoddard, Christiana; Urban, Carly (American Economic Review, 2016)
We examine the effect of a student loan information intervention on changes in college major using administrative data from the Montana University System from 2002-2014. Our difference-in-difference-in-differences strategy exploits the relative trends for students at Montana State University above and below the cutoff for receiving a warning letter about their student debt, compared to their counterparts at the University of Montana. We find that students who receive information suggesting they may be unlikely to be able to repay their loans are more likely to switch to higher earning majors, with higher academic performers most likely to choose STEM fields.